Suppression of Peroxisomal Enzyme Activities and Cytochrome P450 4A Isozyme Expression by Congeneric Polybrominated and Polychlorinated Biphenyls. (13th September 2007) - Robertson, Larry W.; Berberian, Isabelle; Borges, Tim; Chen, Li-Chuan; Chow, Ching K.; Glauert, Howard P.; Filser, Johannes G.; Thomas, Helmut
Abstract : The purpose of this study was to determine the effects of PCBs and PBBs on peroxisome proliferator-activated receptor-α -(PPARα -) associated enzyme activities or protein levels. Male Sprague-Dawley rats were administered a single IP injection (150 μ mol/kg) of either 3, 3′, 4, 4′-tetrabromobiphenyl, 3, 3′, 4, 4′-tetrachlorobiphenyl, 3, 3′, 5, 5′-tetrabromobiphenyl, 2′, 3, 3′, 4, 5-pentachlorobiphenyl, 3, 3′, 4, 4′, 5-pentachlorobiphenyl, 2, 2′, 3, 3′, 5, 5′-hexachlorobiphenyl, or 3, 3′, 4, 4′, 5, 5′-hexabromobiphenyl in corn oil (10 ml/kg). One week later, the activities of catalase, peroxisomal fatty acyl-CoA oxidase, and peroxisomal beta-oxidation as well as cytochrome P450 4A (CYP4A) protein content were determined in subcellular liver fractions. None of the peroxisomal enzyme activities were significantly increased by any of the halogenated biphenyl congeners tested. Except for minor (approx. 25%) increases in the total CYP4A content following treatment with 2, 2′, 3, 3′, 5, 5′-hexachlorobiphenyl and 3, 3′, 5, 5′-tetrabromobiphenyl, CYP4A protein contents were not increased by any treatment. The two Ah receptor agonists, 3, 3′, 4, 4′-tetrabromobiphenyl and 3, 3′, 4, 4′, 5-pentachlorobiphenyl, significantly diminished the liver content of CYP4A proteins and activities of the peroxisomal enzymes studied. Since a range of congeners with different biologic and toxicologic activities were selected for this study, it may be concluded that the polyhalogenated biphenyls do not induce peroxisome proliferation in the male rat, but rather certain members of this class of compounds down regulate peroxisome-associated enzymes. Since PCBs and PBBs do not increase enzyme activities and expression of proteins associated with PPARα, these agents are therefore exerting their carcinogenic and promoting activities by some other mechanism.